People’s technologies in farm sector – a scientific approach for sustainability - K. Narayanagowda; M. Ranganath; B.S. Siddaramaiah (Journal of Agricultural Extension Management, 2025)
People’s technology is local wisdom that is unique to a given culture or society. It is the basis for local level decision making in agriculture, health care, food preparation, education, natural resource management and a host of other activities in rural society. Such knowledge is passed down from generation to generation, in many societies by word of mouth. India has a rich tradition of oral knowledge that goes back to the Vedic times. Much of that wisdom is being rediscovered by the modern world. This is true of Indian agriculture as well. A rich heritage of accumulated indigenous agriculture knowledge is being practiced. But unfortunately the wisdom was passed on either by word of mouth or observation and rarely documented in written form. As a result, the significance of many of the indigenous useful practices is either lost or at times, the practice itself has been distorted